A trend in media and communication research in Malaysia 1987-2005 - Ismail, Rizalawati (World Journalism Education Council, 2016)
The state of media and communication research and education have been undertaken periodically in the United States of America (USA) (Berelson, 1959; Schramm, 1983) and Britain (Carey, 1996; Halloran, 1981). However, no similar published works were identifiable in Malaysia. If any, there were only few published articles by Malaysian scholars that criticized the nature of M&C research in Malaysia as functionalist and policy-oriented (Zaharom Nain, 2001; 2003; Mustafa Kamal, 1992; 2000). This paper presents a small part of a study on the state of media and communications (M&C) research and education in Malaysia. Specifically, this paper investigates the trends of M&C research published in the local journal publications. Riffe and Freitag (1997) used content analysis as a method in their study of 25 years (1987-2005) of research trends through an analysis of Journalism Quarterly. Therefore, this paper identifies research paradigms and methodologies used in the two Malaysian journals on media and communications – Jurnal Pengajian Media (Journal of Media Studies) and Jurnal Komunikasi (Journal of Communication). There are not many M&C journals published in Malaysia and most academic journals are university based or published by the university. For example, Jurnal Pengajian Media is published by University Malaya (UM), while Jurnal Komunikasi is published by Universiti Kebangsaan Malaysia (UKM). A total of 86 research articles related to media and communications published in these two journals between 1987 and 2005. Using content analysis, each article were coded according to (1) research issues, (2) research paradigm, (3) research approach, (4) method of research and (5) data gathering procedures. Results show that half of the research articles (52%) published in JK and JPM are a-theoretical which demonstrates the administrative nature of research. While 48% of published articles did engage with theory, most were using ‘old theories’ borrowed from the effect tradition or administrative paradigm. Less than 10% of the total research examined critical theories such as post-modernism, globalization, Habermas’ critical theory, social semiotics, cultural theory etc.